OPTIMALISASI BISNIS PONDOK PESANTREN DENGAN ELEKTRONISASI SISTEM PEMBAYARAN STUDI KASUS PONDOK PESANTREN NURUL AMANAH BANGKALAN MADURA - Dzikrulloh, Dzikrulloh (Universitas Trunojoyo Madura, 2017)
The research is the optimization of Islamic boarding school business with the electronization of payments at Nurul Amanah Islamic Boarding School in Bangkalan. The electronic payment system that implemented at the Nurul Amanah Islamic Boarding School is called E-Nura (Electronisasi Nurul Amanah).The method of this study is qualitative. This study focuses on how the application of payment system electronization is applied at Nurul Amanah Islamic Boarding School. This study aims to answer the problems that occur in business development in Islamic boarding schools such as capital, loss and business reports.With the payment system electronization system, the problem of economic development in Islamic boarding schools, capital, reports and the effectiveness of goods rotation can be solved. Not only that, e-nura provides security, ease of transaction, speedness, effectiveness and efficiency of transactions and profit optimization in the Nurul Amanah Islamic boarding school business. Thus the application of the payment system electronization in Pondok Pesantren is not only beneficial for the institution but also beneficial for students and parents.